Respuestas
Respuesta dada por:
2
Tenemos que:
![\sqrt[n]{ x^{a} } = x^{ \frac{a}{n}} \sqrt[n]{ x^{a} } = x^{ \frac{a}{n}}](https://tex.z-dn.net/?f=+%5Csqrt%5Bn%5D%7B+x%5E%7Ba%7D+%7D+%3D+x%5E%7B+%5Cfrac%7Ba%7D%7Bn%7D%7D+)
En este caso tenemos:
![\sqrt[3]{ x^{2} }- x^{2} = x^{ \frac{2}{3}}- x^{2} \sqrt[3]{ x^{2} }- x^{2} = x^{ \frac{2}{3}}- x^{2}](https://tex.z-dn.net/?f=+%5Csqrt%5B3%5D%7B+x%5E%7B2%7D+%7D-+x%5E%7B2%7D+%3D+x%5E%7B+%5Cfrac%7B2%7D%7B3%7D%7D-+x%5E%7B2%7D+)
Ahora solo lo ordenamos de mayor a menor:
![- x^{2}+x^{ \frac{2}{3}} - x^{2}+x^{ \frac{2}{3}}](https://tex.z-dn.net/?f=+-+x%5E%7B2%7D%2Bx%5E%7B+%5Cfrac%7B2%7D%7B3%7D%7D)
En este caso tenemos:
Ahora solo lo ordenamos de mayor a menor:
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años